2010
DOI: 10.1259/bjr/16337436
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy computed tomography in pulmonary embolism

Abstract: ABSTRACT. The introduction of modern dual-energy CT (DECT) scanners has enabled contrast material to be distinguished at imaging without the need for a separate unenhanced scan. Images of pulmonary parenchymal contrast enhancement obtained using DECT improve the detection of defects, augmenting our ability to detect pulmonary emboli; however, with these advances new pitfalls are also introduced. In this pictorial review, we present the technique, clinical applications and causes and remedies of false results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 25 publications
0
67
0
1
Order By: Relevance
“…5). Several articles have assessed the role of DECT in the diagnosis of pulmonary thromboembolism (37)(38)(39)(40)(41)(42)(43)(44). Krisska et al (40) obtained a high negative predictive value by using perfusion images.…”
Section: Thorax Applicationsmentioning
confidence: 99%
“…5). Several articles have assessed the role of DECT in the diagnosis of pulmonary thromboembolism (37)(38)(39)(40)(41)(42)(43)(44). Krisska et al (40) obtained a high negative predictive value by using perfusion images.…”
Section: Thorax Applicationsmentioning
confidence: 99%
“…The same assumption was also made in the study by Pontana et al [Pontana F, 2008], in which four subsegmental perfusion defects were depicted by BFI images, whereas endoluminal thrombi were not visualised in the corresponding arteries by CTPA. Zhang et al [Lu GM ,2010] also found a similar so-called false-positive DECT result in one patient with chronic PE in the pulmonary images of BFI. In another patient undergoing anticoagulant therapy, the conventional CTPA performed initially did not visualize abnormal findings.…”
Section: Acute Pe Detectionmentioning
confidence: 74%
“…There are a number of new pitfalls in these perfusion images such as gravity dependent perfusion, pseudo/high perfusion due to dense contrast material in the thoracic veins, cardiac motion, or artefacts caused by underlying pulmonary disease especially emphysema and the reader has to become familiar with them when assessing CT perfusion images (33). Recent studies in small patient groups have found a good correlation between pulmonary perfusion defects seen by DECT perfusion imaging and the gold standard, pulmonary perfusion (SPECT) scintigraphy (34,35).…”
Section: Dual-source Ctmentioning
confidence: 99%